UJI AKTIVITAS SEDIAAN TEH BIJI MAHONI ( Swietenia mahagoni ) UNTUK MENURUNKAN KADAR GLUKKOSA DAN AKTIVITAS PEROKSIDASI LIPID PADA TIKUS DIABETES MILLITUS TIPE 2 - Nielma Auliah; Muhammad Asri (Politeknik Kesehatan Makassar, 2019)
This research aimed to know the effect of mahagony seeds ( Swieteniamahagoni ) tea of MDA levels induced type 2 diabetes mellitus alloxan. By using the control group design method, post-test and by using 15 rats divided into 5 groups, namely group I negative group, group II control Alloxan induction, group III tea mahagony seeds 5 gram/kgBB, group IV tea mahagony seeds 10 gram/kgBB and group V mahagony seeds 15 gram/kgBB. The treatment was carried out for 14 days. In this research showed that the level of blood glucose affects increase of MDA levels. At 15 gram/kgBBof tea dosage presentasionshowed a significant value on decreasing blood glucose levels P = 0,000 < (α 0,05) and blood MDA levels P = 0,000 < (α 0,05) and it can be concluded that mahogany seed tea (Swieteniamahagoni) had an effect on decreasing levels of rat MDA type 2 diabetes mellitus induced by alloxan, with a dose of 15 grams /kgBB which is the optimal dose in reducing blood Glucose and MDA levels. Keywords : Type 2 Diabetes Mellitus, MDA, Mahogany Seeds Tea, Alloxan